Chemical Separation on Silver Nanorods Surface Monitored by TOF-SIMS - Ondrej Petruš; Andrej Oriňak; Renáta Oriňaková; Christian Muhmann; Ján Macko; Radim Hrdý; Jaromír Hubálek; Branislav Erdelyi; Heinrich F. Arlinghaus (Journal of Chemistry)
The article introduces a possible chemical separation of a mixture of two compounds on the metal nanorods surface. A silver nanorods surface has been prepared by controlled electrochemical deposition in anodic alumina oxide (AAO) template. Rhodamine 6G and 4-aminothiophenol have been directly applied to the sampling point on a silver nanorods surface in an aliquot mixture. The position of the resolved compounds was analysed by time-of-flight secondary ion mass spectrometry (TOF-SIMS) which measured the fragments and the molecular ions of the two compounds separated on the silver nanorods surface. Rhodamine 6G has been preconcentrated as 1.5 mm radial from the sampling point while 4-aminothiophenol formed a continuous self-assembled monolayer on the silver nanorods surface with a maximum molecular ion intensity at a distance of 0.5 mm from the sampling point. The separation of the single chemical components from the two-component mixture over the examined silver nanostructured films could clearly be shown. A fast separation on the mentioned nanotextured films was observed (within 50 s). This procedure can be easily integrated into the micro/nanofluidic systems or chips and different detection systems can be applied.